Case Report: MRI, Clinical, and Pathological Correlates of Bromethalin Toxicosis in Three Dogs - Murthy, Vishal D.; McLarty, Ehren; Woolard, Kevin D.; Parker, Rell L.; Kortz, Gregg; King, Jamie N.; Poppenga, Robert H.; Knipe, Marguerite F.; Dickinson, Peter J. (Frontiers in Veterinary Science, 2022)
Bromethalin toxicosis is an increasingly common clinical presentation in dogs that may be fatal depending on extent of intoxication. Antemortem diagnosis of bromethalin toxicosis was achieved in 3 dogs by demonstration of the active metabolite desmethylbromethalin in fat or serum. Magnetic resonance imaging (MRI) findings were consistent with a diffuse leukoencephalopathy with restricted diffusion and prominent involvement of the corticospinal motor tracts on T2-weighted and diffusion-weighted sequences. Imaging findings were confirmed in one non-surviving dog at necropsy. Resolution of MRI abnormalities was demonstrated in one surviving dog that was consistent with associated resolution of clinical signs. Initial findings in these dogs support further investigation of specific MRI patterns in cases of leukoencephalopathy to aid differential diagnosis. While antemortem detection of bromethalin and its metabolites confirms exposure, quantitation may be informative as a prognostic biomarker.